Environmental drivers of succession in jack pine-dominated stands of boreal Ontario - Longpre, Trevor William F. (2007)
Spanning boreal Ontario, photo chronosequencing was used to observe change through time in 178 stands comprised at least in part by jack pine (Pinus bansiana Lamb.). Linked to growth and yield monitoring plot networks and a national climate model, observed succession was associated to 17 environmental attributes specific to geographic location, topography, soil conditions, and climate. Through the application of two non-parametric analytical techniques: regression trees and survival analysis, three fundamental ecological relationships to succession were identified. Deep sands were found to be the most influential ecological driver of succession in jack pine-dominated stands of boreal Ontario, followed by slope gradient and precipitation during the growing season. Derived cumulative survival probability functions for each of these variables offers tangible means by which forest forecast models in the region can be empirically refined.